Interplay between Users and Social Media: “Pin” in WeChat Moments as an Example: From an Affordance Perspective - Yu, Shuyang (Transactions on Social Science, Education and Humanities Research, 2024)
This paper explores the newly released WeChat feature “pin” as an example to explore the gap in current research on affordance theory. WeChat, as the leading social media in China, displays distinct Chinese characteristics of socialization, which thus requires an in-depth investigation not only into the mechanism itself but also into the users’ psychology. Therefore, the author points out the theoretical gap in extant literature that the subject-object dichotomy hinders scholars from a more comprehensive study of social media and strives to promote a methodological revolution to combine the two categories. Modeled after the division of affordances’ emergence, perception, and actualization, this paper tentatively discusses the potential effects of “pin” on both posters and receivers in WeChat Moments. Most importantly, with a proposal for the revolution of extant theoretical methodology, this paper is aimed at providing a new perspective for ongoing research and encouraging an innovative model in future studies.